Lipidomic Analyses of Female Mice Lacking Hepatic Lipase and Endothelial Lipase Indicate Selective Modulation of Plasma Lipid Species. Issue 6 (29th April 2014) - Yang, Yanbo; Kuwano, Takashi; Lagor, William R.; Albert, Carolyn J.; Brenton, Siobhan; Rader, Daniel J.; Ford, David A.; Brown, Robert J.
Abstract: Hepatic lipase (HL) and endothelial lipase (EL) share overlapping and complementary roles in lipoprotein metabolism. The deletion of HL and EL alleles in mice raises plasma total cholesterol and phospholipid concentrations. However, the influence of HL and EL in vivo on individual molecular species from each class of lipid is not known. We hypothesized that the loss of HL, EL, or both in vivo may affect select molecular species from each class of lipids. To test this hypothesis, we performed lipidomic analyses on plasma and livers from fasted female wild‐type, HL‐knockout, EL‐knockout, and HL/EL‐double knockout mice. Overall, the loss of HL, EL, or both resulted in minimal changes to hepatic lipids; however, select species of CE were surprisingly reduced in the livers of mice only lacking EL. The loss of HL, EL, or both reduced the plasma concentrations for select molecular species of triacylglycerol, diacylglycerol, and free fatty acid. On the other hand, the loss of HL, EL, or both raised the plasma concentrations for select molecular species of phosphatidylcholine, cholesteryl ester, diacylglycerol, sphingomyelin, ceramide, plasmanylcholine, and plasmenylcholine. The increased plasma concentration of select ether phospholipids was evident in the absence of EL, thus suggesting that EL might exhibit a phospholipase A2 activity. Using recombinant EL, we showed that it could hydrolyse the artificial phospholipase A2 substrate 4‐nitro‐3‐(octanoyloxy)benzoic acid. In summary, our study shows for the first time the influence of HL and EL on individual molecular species of several classes of lipids in vivo using lipidomic methods.